Diagnosis of potential stressors adversely affecting benthic invertebrate communities in Greenwich Bay, Rhode Island, USA. (12th August 2016) - Pelletier, Marguerite; Ho, Kay; Cantwell, Mark; Perron, Monique; Rocha, Kenneth; Burgess, Robert M.; Johnson, Roxanne; Perez, Kenneth; Cardin, John; Charpentier, Michael A.
Abstract: Greenwich Bay is an urbanized embayment of Narragansett Bay potentially impacted by multiple stressors. The present study identified the important stressors affecting Greenwich Bay benthic fauna. First, existing data and information were used to confirm that the waterbody was impaired. Second, the presence of source, stressor, and effect were established. Then linkages between source, stressor, and effect were developed. This allows identification of probable stressors adversely affecting the waterbody. Three pollutant categories were assessed: chemicals, nutrients, and suspended sediments. This weight of evidence approach indicated that Greenwich Bay was primarily impacted by eutrophication‐related stressors. The sediments of Greenwich Bay were carbon enriched and low dissolved oxygen concentrations were commonly seen, especially in the western portions of Greenwich Bay. The benthic community was depauperate, as would be expected under oxygen stress. Although our analysis indicated that contaminant loads in Greenwich Bay were at concentrations where adverse effects might be expected, no toxicity was observed, as a result of high levels of organic carbon in these sediments reducing contaminant bioavailability. Our analysis also indicated that suspended sediment impacts were likely nonexistent for much of the Bay. This analysis demonstrates that the diagnostic procedure was useful to organize and assess the potential stressors impacting the ecological well‐being of Greenwich Bay. This diagnostic procedure is useful for management of waterbodies impacted by multiple stressors. Environ Toxicol Chem 2017;36:449–462. © 2016 SETAC